Reliability and validity evidence for the French Psychological Need Thwarting Scale (PNTS) scores: Significance of a distinction between thwarting and satisfaction of basic psychological needs. (September 2015) - Martinent, Guillaume; Guillet-Descas, Emma; Moiret, Sophie
Abstract: Objectives: The goal of these studies was to provide evidence of the significance of a distinction between basic psychological need thwarting (BPNT) and satisfaction (BPNS) within a sport context. Studies 1a and 2 tested the score validity and reliability of the French PNTS (Psychological Need Thwarting Scale) for measuring BPNT for autonomy, competence, and relatedness. Study 1b examined the relationships between BPNT and selected variables (athlete burnout and sport motivation) by controlling for BPNS. Method: Participants in study 1 ( N study 1a = 239; N study 1b = 132) and study 2 ( N = 132) were adolescents athletes who completed the PNTS and other questionnaires. Data were analyzed with internal consistency, average variance extracted, composite reliability, confirmatory factor analyses (studies 1a and 2) and correlational analyses (studies 2 and 1b). Design: Cross-sectional. Results: Results of studies 1a and 2 showed that the 11-item 3-factor correlated structure of the PNTS fitted the data adequately. Multiple-group CFAs showed that the PNTS scores were partially invariant across the samples from studies 1a and 2. In study 2, BPNS positively correlated with self-determined forms of motivation and negatively correlated with controlled forms of motivation and/or athlete burnout whereas BPNT showed the opposite pattern of results. In study 1b, BPNT was associated with athlete burnout and sport motivation after BPNS was held constant. Conclusions: This study provided support for the reliability and validity of the French PNTS scores (studies 1a and 2) and the incremental validity of BPNT (study 1b), supporting the distinction between BPNS and BPNT. Highlights: The 11-item 3-factor structure of the French PNTS fitted the data adequately. BPN thwarting significantly correlated with burnout, motivation and BPN satisfaction. BPN satisfaction was associated with selected outcomes controlling for BPN thwarting. BPN thwarting was associated with selected outcomes controlling for BPN satisfaction. The three studies strongly supported the distinction between BPN satisfaction and thwarting.